2015
DOI: 10.1586/14787210.2015.1033400
|View full text |Cite
|
Sign up to set email alerts
|

Darunavir/cobicistat once daily for the treatment of HIV

Abstract: A current focus in HIV management is improving adherence by minimizing pill burden with convenient formulations, including fixed-dose combinations (FDCs). Darunavir, a HIV protease inhibitor, co-administered with low-dose ritonavir (800/100 mg once daily), is recommended in guidelines in combination with other antiretrovirals for HIV patients with no darunavir resistance-associated mutations. Cobicistat is an alternative agent to ritonavir for boosting plasma drug levels of darunavir among other antiretroviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“… *The postpartum visit darunavir AUC 24 h and C 0 h were similar to those observed in a historical phase 3b study of HIV‐1‐infected adults treated with a darunavir/cobicistat‐based regimen (mean ± SD AUC 24 h : 102 000 ± 33 100 ng h/mL; C 0 h : 2150 ± 1320 ng/mL) . † For within‐subject comparisons, BLQ values were excluded for C min ; second trimester, n = 6; third trimester, n = 6; and postpartum, n = 5.…”
Section: Resultsmentioning
confidence: 79%
“… *The postpartum visit darunavir AUC 24 h and C 0 h were similar to those observed in a historical phase 3b study of HIV‐1‐infected adults treated with a darunavir/cobicistat‐based regimen (mean ± SD AUC 24 h : 102 000 ± 33 100 ng h/mL; C 0 h : 2150 ± 1320 ng/mL) . † For within‐subject comparisons, BLQ values were excluded for C min ; second trimester, n = 6; third trimester, n = 6; and postpartum, n = 5.…”
Section: Resultsmentioning
confidence: 79%
“…DRV is extensively metabolized by cytochrome P450 (CYP), mainly CYP3A . COBI is a potent mechanism‐based inhibitor of CYP3A and thus a pharmacoenhancer of DRV …”
mentioning
confidence: 99%
“…In Phase I trials, cobicistat was shown to be a comparable therapeutic enhancer to ritonavir in combination with atazanavir, integrase inhibitor elvitegravir, or midazolam (a CYP3A test substrate) [52]. An atazanavir / cobicistat dependent regimen provided efficacy and protection comparable to an atazanavir / ritonavir regimen in phase II studies [50]. However, a randomized trial at the Shanghai Public Health Clinical Center (SPHCC) evaluating Cobicistat for COVID-19 has shown that it has not been successful and can be reassessed.…”
Section: Cobicistatmentioning
confidence: 99%
“…The Chinese authorities have indicated that Darunavir against 2019-nCoV may be successful. In vitro cell studies have shown that Darunavir can effectively inhibit replication of the new strain, at a concentration of 300 micromolar, according to preliminary research Darunavir, in conjunction with cobicistat, will be used in patients with COVID-19 pneumonia in trial number NCT04252274 (50). Such a mixture is currently approved by the United States Food and Drug Administration (FDA) in AIDS treatment.…”
Section: Darunavirmentioning
confidence: 99%